2015
DOI: 10.1111/pere.12109
|View full text |Cite
|
Sign up to set email alerts
|

Family process: Early child emotionality, parenting stress, and couple relationship quality

Abstract: Guided by family systems theory, we used couple data (N = 1,778) from the Fragile Families and Child Wellbeing Study to examine the link between perceived infant negative emotionality, parenting stress, and couple relationship quality when the child was 1, 3, and 5 years. Using a latent actor-partner interdependence model, we tested dyadic direct and indirect effects for married and cohabiting couples. Parents who reported higher levels of perceived infant negative emotionality at age 1 had higher parenting st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 55 publications
2
23
0
2
Order By: Relevance
“…Temperament score at age one is significantly correlated with externalizing behavior at age five among FFCWS participants [27]. Consistent with previous FFCWS analyses using this temperament scale [27][28][29], factor analysis indicated that the three items represented a single factor, with moderate internal consistency (Cronbach's alpha = 0.60). We summed standardized factor loadings for each of the items to generate a weighted score for temperament with a mean of zero and a standard deviation of approximately one.…”
Section: Methodssupporting
confidence: 81%
“…Temperament score at age one is significantly correlated with externalizing behavior at age five among FFCWS participants [27]. Consistent with previous FFCWS analyses using this temperament scale [27][28][29], factor analysis indicated that the three items represented a single factor, with moderate internal consistency (Cronbach's alpha = 0.60). We summed standardized factor loadings for each of the items to generate a weighted score for temperament with a mean of zero and a standard deviation of approximately one.…”
Section: Methodssupporting
confidence: 81%
“…The use of person‐centered analyses in cross‐sectional and longitudinal studies also helped advance the understanding of patterned variation among families (e.g., Oxford & Lee, ; Pratt, McClelland, Swanson, & Lipscomb, ; Withers, McWey, & Lucier‐Greer, ; Yan & Ansari, ). Although selection effects continued to be underexamined, some studies were sensitive to these possible explanatory characteristics in change predictions (e.g., Blake Berryhill, Soloski, Durtschi, & Reyes Adams, ; Chang et al, ; Mustillo et al, ; Zvara et al, ). Parent and youth gender received attention during the past decade and increased the specificity of some findings during the past decade, but theories and models that integrated gender similarities and differences in family processes were limited.…”
Section: Concluding Comments and Future Directionsmentioning
confidence: 99%
“…Second, fathers' supportive coparenting significantly buffered the effects of mothers' parental stress on relationship quality, but parental stress was not predictive of either parent's relationship quality (Durtschi et al, ). Finally, mothers' and fathers' parenting stress was related to lower levels of couples' relationship quality 2 years later (Berryhill, Soloski, Durtschi, & Adams, ). Additional research on the transition to parenthood and parents who have children with disabilities and health problems (mental and physical) gives credence to the negative association between parenting stress and couples' relationship quality (Gupta, ; Quittner, Glueckauf, & Jackson, ; Schulz, Cowan, & Cowan, ).…”
Section: Introductionmentioning
confidence: 99%